Buckling of slender composite piles in soft soils - A comparative study between the Swedish analytical method and 3D Finite Element - Nordström, Rasmus (My University, 2020)
When designing piles in Sweden today an analytic method is used exclusively to calculate the piles structural bearing capacity with regards to buckling (buckling of the 2nd order). A geometrical instability arises when composite piles, made from steel and concrete, are designed according to Eurocode 4 "Design of composite structures". While the Swedish analytical method consider the plastification of the surrounding soil with elastic conditions in the pile member. These assumption in both methods rises the question of how to design for ULS with composite piles. The study was made as a comparison between the traditional Swedish analytical method and a 3D numerical model using the program Tochnog Professional. The numerical model was shown to replicate the real life failure mechanisms of buckling of a composite slender pile, but yield point was off. A reason might be the difficulty of modeling the confinement effects of the concrete part of the model. The study concluded that the numerical model overpredicts the capacity compared to the analytical when the soil is the design factor for capacity and underpredicts the capacity when the cross section is the design factor for capacity. The most critical parameter for the analytical method is the initial bow imperfection. This is something that is not modeled in the numerical model because of restrictions in the modeling process.
Keywords: Buckling of composite piles; slender piles; Swedish pile commision report 96; soft soil; Tochnog Professional